Thinking in Stories: Narrative Reasoning of an Occupational Therapist Supporting People with Profound Intellectual Disabilities' Engagement in Occupation. Issue 1 (3rd January 2023) - Haines, David; Wright, Jon
Abstract: This article illustrates narrative reasoning using the findings from research into an occupational therapy intervention promoting changes in the ways a staff team facilitated meaningful engagement in occupation. Qualitative critical ethnographic case study research explored a single case over one year of an occupational therapist working with five people with profound intellectual disabilities and their support network. Data were collected using participant observation, interviews and document analysis. Illustrated by an ethnodramatic vignette, the findings demonstrate how the occupational therapist reasoned narratively by eliciting, telling and creating stories and how this supported individualization of her intervention to the specific context. Creation of a prospective story that the support network were invited to share, guided and propelled the intervention toward its hoped-for ending. Narrative reasoning was particularly apparent in opportunities to reflect aloud, supporting occupational therapists' need of opportunities for reflection through story-sharing and story-making. Case study and ethnographic research methodologies may be useful in further clinical reasoning research to better understand narrative reasoning.